1、 [(x+二分之一y)平方+(x-二分之一y)平方](2x平方-二分之一y平方)

1个回答

  • [(x+y/2)^2+(x-y/2)^2](2x^2-y^2/2)

    =[(x^2+xy+y^2/4/2)+(x^2-xy+y^2/4/2)](2x^2-y^2/2)

    =(2x^2+y^2/2)(2x^2-y^2/2)

    =4x^4-y^4/4

    (2x-y+2)(y-2x+2)

    =(2+2x-y)(2-2x+y)

    =(2+2x-y)[2-(2x-y)]

    =2^2-(2x-y)^2

    =4-(4x^2-4xy+y^2)

    =4-4x^2+4xy-y^2

    (2+1)(2^2+1)(2^4+1)(2^8+1)(2^16+1)

    =(2-1)(2+1)(2^2+1)(2^4+1)(2^8+1)(2^16+1)

    =(2^2-1)(2^2+1)(2^4+1)(2^8+1)(2^16+1)

    =(2^4-1)(2^4+1)(2^8+1)(2^16+1)

    =(2^8-1)(2^8+1)(2^16+1)

    =(2^16-1)(2^16+1)

    =2^32-1

    三个连续整数为:n-1,n,n+1

    n-1+n+n+1=(n-1)*n*(n+1)

    3n=n(n^2-1)

    n(n^2-1)-3n=0

    n(n^2-1-3)=0

    n(n^2-4)=0

    n(n-2)(n+2)=0

    n=0 或 n=2 或 n=-2

    当n=0时

    三个连续整数为:-1,0,1

    当n=2时

    三个连续整数为:1,2,3

    当n=-2时

    三个连续整数为:-3,-2,-1